The Risk Factors of Postoperative Delirium after Total Knee Arthroplasty - Wang, Lih; Seok, Sangyun; Kim, Sungsoo; Kim, Kyungtaek; Lee, Seunghyun; Lee, Kyungho (The Journal of Knee Surgery, 2017)
We investigated the results of delirium which developed after total knee arthroplasty (TKA) and the risk factors for delirium in the patients who are older than 65 years. From March 2008 to March 2012, we performed a retrospective study on 296 knees of 265 patients who were treated with TKA. They were divided into two groups: 216 patients without delirium and 49 patients diagnosed with delirium by psychiatry. We analyzed the risk factors into three categories: First, the preoperative factors including gender, age, body mass index (BMI), clinical and functional knee joint score (Knee Society Knee Score and Knee Society Function Score) and the number of underlying diseases and associations with each disease; Second, the operative factors including the anesthesia method, amount of blood loss, operating time, laboratory factors, and transfusion count; Third, the postoperative factors such as start time of walking and duration of hospital stay were analyzed. There were significant statistical difference between two groups just in age, history of dementia, cerebrovascular disease, difference of hemoglobin and albumin, start time of walking, and duration of hospital stay. The delirium after TKA delays the postoperative ambulation and extends the hospital stay, which causes functional and socioeconomic loss of patients. Therefore, the risk factors for delirium should be assessed and proper prevention and management should be conducted.
Keywords: delirium; total knee arthroplasty; risk factors